Bibliometric Investigation of Development and Research Trends in Transformative Education: A Comprehensive Analysis on Scopus Database (1983-2023) - Shidiq, M. Syahrul; Maksum, Muh. Nur Rochim; Narimo, Sabar (Universitas Muhammadiyah Surakarta, 2023)
Employing bibliometric analysis techniques, the research delves into all Scopus-database-indexed publications on Transformative Education spanning the years 1983 to 2023. Data analysis was conducted using Excel and R/R-Studio, with VOSviewer employed to visually depict the concurrent presence of keywords and document quotations. A total of 4484 publications meeting the specified criteria were identified. The findings reveal an annual growth rate of 9.26%, with the highest number of publications in the year 2022. Notably, the United States emerges as the leading contributor to these publications, predominantly affiliated with the University of Toronto. The most prolific author in the realm of transformative education is identified as Zembylas, M (Pavlidis, 2015). It's important to note that the bibliometric analysis was confined to Scopus data, and broader inclusion of other national and international databases would have enhanced the comprehensiveness of the study. In presenting a concise overview of the accessible literature in the education field, this study also provides recommendations for future research endeavors.